The Impact of Fibromyalgia in Spondyloarthritis: From Classification Criteria to Outcome Measures - Alunno, Alessia; Carubbi, Francesco; Stones, Simon; Gerli, Roberto; Giacomelli, Roberto; Baraliakos, Xenofon (Frontiers in Medicine, 2018)
The term spondyloarthritis (SpA) encompasses a broad clinical spectrum characterized by chronic inflammatory conditions affecting the sacroiliac joints, the spine but also peripheral joints and tendons and being additionally associated with the involvement of organs, such as bowel, eye and skin (1). Musculoskeletal pain is a key symptom in SpA. However, although low back pain and/or joint pain are characteristic for SpA, undifferentiated pain at different enthesial sites may also be a concomitant or even the first clinical presentation in some patients (2). In addition, fatigue is another important symptom often reported by patients with SpA, which substantially affects the quality of life (QoL) (3). Fibromyalgia (FM) is the most common diagnosis in patients complaining of chronic diffuse pain with fatigue and may occur alone or in association with chronic inflammatory diseases (4). The prevalence of FM ranges from 2 to 8% in the general population and it can reach up to over 50% in patients with other rheumatic and musculoskeletal diseases (RMDs) (5–7). FM has been identified as the most disabling RMD, based on the patients' perception that their medical condition is not properly recognized (8). This is also due to the poor knowledge about its pathogenesis, and therefore the lack of reliable biomarkers reveals a major unmet need requiring to be addressed in further research studies. Over the last decade, an increasing body of evidence described the impact of FM in SpA highlighting the pitfalls for correct classification, appropriate differential diagnosis and assessment of outcome measures in both conditions. The purpose of this review is to provide an overview of currently available data with regard to the coexistence and reciprocal features of FM and SpA.